2015
DOI: 10.1155/2015/623890
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between Experiences of Bereaved Relatives, Physicians, and Nurses with Hospital End-of-Life Care: Everyone Has Their “Own Truth”

Abstract: When patients die relatives and healthcare professionals may appreciate the quality of the dying phase differently, but comparisons are rare. In a cross-sectional study (June 2009–July 2012) the experiences of bereaved relatives, physicians, and nurses concerning the quality of dying in a large Dutch university hospital were compared, and the relation to communication was explored. Measurements were concordance on the quality of dying (QOD) (0–10 scale), awareness of impending death, and end-of-life communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…From other research it is known that perspectives of relatives can differ from those of the patient or the physician. [ 34 ] We did not have information on the non-responders, so selection bias cannot be ruled out. As this study was performed in a single, academic centre, the generalizability of the findings may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…From other research it is known that perspectives of relatives can differ from those of the patient or the physician. [ 34 ] We did not have information on the non-responders, so selection bias cannot be ruled out. As this study was performed in a single, academic centre, the generalizability of the findings may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that experiences with end of life care of professionals and bereaved relatives may differ. 16 Symptom burden. Other studies found varying prevalences of pain (20%-57%), breathlessness (48%-84%) and agitation (23%-77%) among patients with COVID-19 in the last phase of life.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Healthcare professionals and relatives sometimes have different perceptions of how much prognostic information relatives have been given. 21,22 It is therefore important to consider a range of perspectives when addressing this issue.…”
Section: Introductionmentioning
confidence: 99%